Planning for a Successful Commercial Subtropical/Tropical Fruit Grove - Jonathan Henry Crane; Yuncong Li; Edward A Evans; Fredy H Ballen; Jeff Wasielewski (EDIS)
Planning is the key to successful grove establishment, maintenance, and production. Developing a detailed infrastructure description and plan, cultural program, and financial and marketing plan for a new or existing grove with a new fruit crop will save you time and money and help minimize mistakes. Prospective growers should compile and analyze information needed to select a grove site, establish the needed infrastructure, and develop maintenance plans for the plants and how the production will be marketed. This new 15-page publication of the UF/IFAS Horticultural Sciences Department presents an outline of the type of information growers need when establishing a tropical fruit grove or contemplating management or modification of an existing grove. Written by Jonathan Crane, Yuncong Li, Edward Evans, Fredy Ballen, and Jeff Wasielewski. https://edis.ifas.ufl.edu/hs1387